Pedagogical practices and civic knowledge and engagement in Latin America : multilevel analysis using ICCS data (2023)
RESUMEN: This study explored the relationship between pedagogical practices and the civic knowledge and engagement of students from five Latin American and Caribbean countries, using a multilevel analysis of the 2016 International Civic and Citizenship Education Study (ICCS). The results reveal the complex interplay of educational, sociodemographic, and attitudinal factors in shaping the civic knowledge and engagement of students. Extracurricular civic engagement showed a negative correlation with student civic knowledge and engagement as measured by the ICCS cognitive test. However, civic learning in school positively related to cognitive abilities, emphasizing the importance of integrating civic learning into the curriculum. Interestingly, students' educational aspirations emerged as a significant factor shaping their civic engagement, suggesting a strategy to foster high educational aspirations to enhance cognitive performance. Additionally, gender dynamics were evident in civic education, with girls consistently outperforming boys in all participating countries. The correlation between home literacy resources and test scores illuminated the significant role of home environments in academic achievement. Lastly, students’ attitudes towards political participation had a notable connection to civic knowledge outcomes, presenting an exciting avenue for future research. Collectively, these findings underscore the need for a comprehensive approach to civic education and further research to refine effective strategies.